Basic Concept of Cell: A Narrative Review - Hidayat, Rachmat; Joko Marwoto; Lusia Hayati (Open Access Indonesian Journal of Medical Reviews, 2021)
All body functions depend on cell integrity. Therefore, understanding cell biology is intrinsically important for understanding disease. A vast amount of information reveals how the cell behaves like an organism with many social cells. At the heart of cell biology is cell communication—how messages originate and are transmitted, received, interpreted, and used by cells. This efficient communication between, and within the cell maintains the function of the cell and its specialization. Intercellular signals enable each cell to determine its position and specific role. Cells must demonstrate a "chemical preference" for other cells and the environment that surrounds them to maintain the integrity of the whole organism. When they no longer tolerate this preference, the conversation ends and the cell adapts (sometimes changes in function) or becomes vulnerable to isolation, injury, illness, or even death. This review explains the function of each component in the cell and its role in life.